2018
DOI: 10.1177/2042098618776541
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical factors predicting warfarin sensitivity after cardiac surgery

Abstract: Background: Warfarin is commonly initiated post-cardiac surgery to reduce the risk of intracardiac thrombus formation. Studies have found that sensitivity is increased after cardiac surgery and anticoagulation is subsequently difficult to manage. This study set out to identify clinical markers of increased warfarin sensitivity in patients after cardiac surgery, and build a model that can predict warfarin sensitivity, and improve safety in this setting. Methods: The study was an observational, retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the risk factors of bleeding during hospitalization are different from outpatients, they were treated in a various physiological and pathological state. 15 Studies have also found that patients are more sensitive to warfarin after valve replacement, 17,18 it means that the therapeutic strategy of AF is different from valve replacement, which requires a lower warfarin dose at initial stage. Hence, existing prediction models may not be suitable for predicting bleeding risk in valve replacement patients during a hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk factors of bleeding during hospitalization are different from outpatients, they were treated in a various physiological and pathological state. 15 Studies have also found that patients are more sensitive to warfarin after valve replacement, 17,18 it means that the therapeutic strategy of AF is different from valve replacement, which requires a lower warfarin dose at initial stage. Hence, existing prediction models may not be suitable for predicting bleeding risk in valve replacement patients during a hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Warfarin is a commonly prescribed oral anticoagulant for patients who have undergone cardiac surgery and remains the only guideline-endorsed anticoagulant for patients with mechanical heart valves. However, considerable interindividual variability exists in the response to warfarin, with patient age, BMI, concomitant medications, and genetic status imparting considerable influence on warfarin maintenance dose requirements [1][2][3][4][5]. Complicating matters in cardiac surgery patients is an exaggerated sensitivity to the effects of warfarin in the immediate postoperative period, predisposing individuals to supratherapeutic international normalized ratio (INR) values and bleeding [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Then liver congestion may affect the metabolism of warfarin and the synthesis of coagulation factors. Since warfarin is 99% bound to plasma proteins (mainly albumin), hypoalbuminemia is caused by in ammation response or blood dilution during CPB, which may also amplify the anticoagulant effect of warfarin [20] . Therefore, traditional warfarin dose prediction algorithms may not be suitable for patients after aortic surgery.…”
Section: Introductionmentioning
confidence: 99%